2012
DOI: 10.1371/journal.pone.0038901
|View full text |Cite
|
Sign up to set email alerts
|

Low Serum Glutathione Peroxidase Activity Is Associated with Increased Cardiovascular Mortality in Individuals with Low HDLc’s

Abstract: Background Since oxidized LDL is thought to initiate atherosclerosis and the serum glutathione peroxidase (GPx3) reduces oxidized lipids, we investigated whether high GPx3 activity reduces cardiovascular disease (CVD) mortality. Methods We determined GPx3 in stored samples from the Minnesota Heart Survey of 130 participants who after 5 to 12 years of follow-up had died of CVD and 240 controls. Participants were 26 to 85 years old and predominantly white. In a nested cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 25 publications
0
37
0
1
Order By: Relevance
“…It has been shown that HO-1 gene transfer inhibits atherosclerosis in apoliporotein E-deficient (ApoE K/K ) mice as well as graft arteriosclerosis and vascular remodeling in rat arteries (Juan et al 2001, Bouchet et al 2002. Apart from HO-1, other Nrf2 downstream targets, such as NQO1, GPx, and Prx I, appear to be involved in the reduction of oxidative damage in the endothelium or arteries during the atheroprotective process (Buijsse et al 2012). Taken together, these data indicate that Nrf2 is an important component in protecting against the pathogenesis of atherosclerosis.…”
Section: Nrf2 and Atherosclerosismentioning
confidence: 99%
“…It has been shown that HO-1 gene transfer inhibits atherosclerosis in apoliporotein E-deficient (ApoE K/K ) mice as well as graft arteriosclerosis and vascular remodeling in rat arteries (Juan et al 2001, Bouchet et al 2002. Apart from HO-1, other Nrf2 downstream targets, such as NQO1, GPx, and Prx I, appear to be involved in the reduction of oxidative damage in the endothelium or arteries during the atheroprotective process (Buijsse et al 2012). Taken together, these data indicate that Nrf2 is an important component in protecting against the pathogenesis of atherosclerosis.…”
Section: Nrf2 and Atherosclerosismentioning
confidence: 99%
“…In adolescents, low serum glutathione was an independent risk factor for parental coronary heart disease risk [45]. Moreover, low GPx levels, for which glutathione is a cofactor, combined with low high-density lipoprotein levels may be partly responsible for increased atherosclerosis-related mortality rates in humans [46]. Nrf2 was identified as an important regulator of GPx in mice [47], and therefore taken together, these data demonstrate that Nrf2 is an important component in protection against the pathogenesis of atherosclerosis.…”
Section: Nrf2 As An Antiatherogenic Factormentioning
confidence: 99%
“…GPx deficient mice display an increased level of oxidised LDL and foam cell formation in arteries [8]. Furthermore, a reduced GPx activity is associated with an increased risk of CVD in humans [9,10]. The promotion of GSH synthesis should therefore increase GPx activity and reduce the levels of oxidised lipids and associated CVD risk.…”
Section: Introductionmentioning
confidence: 99%